Pregunta
upstudy study bank question image url

4. a A dealer made a profit of \( 22 \frac{1}{2} \% \) by selling a car for GHC \( 5,880.00 \). Find the percentage profit he would have realized if he had sold it for GHC \( 6,120.00 .2 \mathrm{~cm} \) to 2 km on the distance axis. b. The sum of four consecutive even numbers is 28 . Find the numbers. c. Solve the following system of linear equations in two variables using the elimination method. \( x+y=1 x+y=1 x+y=1 \) and \( x-y=3 x-y=3 x-y=3 \).

Ask by Olson Burns. in Ghana
Feb 10,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

a. The dealer would make a 27.5% profit by selling the car for GHC 6,120. b. The four consecutive even numbers are 4, 6, 8, and 10. c. The solution is x = 2 and y = -1.

Solución

¡Inicia sesión para desbloquear respuestas gratis!

Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.

star-icon Descubrir

Respondido por UpStudy AI y revisado por un tutor profesional

Beyond the Answer

To find the percentage profit if the car was sold for GHC 6,120.00, we first need to determine the cost price (CP). If a profit of \( 22 \frac{1}{2} \% \) is earned on a selling price (SP) of GHC 5,880.00, we can express this as \( SP = CP + (22.5\% \text{ of } CP) \). By solving this, we find the CP is GHC 4,800.00. If sold for GHC 6,120.00, the profit is GHC 6,120.00 - GHC 4,800.00 = GHC 1,320.00. The profit percentage is then \( \left( \frac{1,320}{4,800} \times 100 \right) \approx 27.5\% \). Now, on to finding those consecutive even numbers! Let's denote those four consecutive even numbers as \( x, x+2, x+4, x+6 \). Together they add up to 28, which gives us \( x + (x+2) + (x+4) + (x+6) = 28 \). Simplifying that yields \( 4x + 12 = 28 \). Therefore, \( 4x = 16 \) and \( x = 4 \). Thus, the numbers are 4, 6, 8, and 10. Easy peasy! For the system of equations given, actually, you've repeated the equation \( x + y = 1 \) three times, which doesn't affect solving. The second equation \( x - y = 3 \) is valid. From \( x + y = 1 \), we can express \( y = 1 - x \). Substituting into \( x - y = 3 \) gives \( x - (1 - x) = 3 \) or \( 2x - 1 = 3 \). Solving this, we find \( x = 2 \) and substituting back to find \( y = 1 - 2 = -1 \). So the solution to the system is \( (2, -1) \)!

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad